An Analysis Of Intrinsic Elements And The Portrayal Of Anxiety In Linkin Park’s Song Lyrics - Ika Oktaria Cahyaningrum (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
This thesis is aimed to analyse the types of intrinsic elements and the portrayal of anxiety in Linkin Park’s song lyrics entitled Numb, In The End, Crawling, Faint, and Breaking The Habit. This thesis applied theories from Culler (2000), Childs and Fowler (2006).This research is descriptive qualitative research. The data in this research are lyrics in Linkin Park’s song. The data are performed by categorizing the lyrics to the types of intrinsic elements. The types observed to find out the portrayal of anxiety. The researcher uses document analysis to get the data. In analyse the data, the researcher uses New Criticism. In validate the data, the researcher used triangulation theory.The research findings show that the researcher found 237 total data of Linkin Park song lyrics from those five songs. The data are classified into the types of intrinsic elements which consist of Ambiguity (14 data), Paradox (7 data), Irony (18 data), Tension (150 data) and Imagery (169 data). Of the data, Tension and Imagery types are more dominant than the other types. It portrayed the anxiety about fear, worry, stress, disappointed, sad, confused, and frustrated.